ANALISIS PENENTUAN SEKTOR EKONOMI STRATEGIS DALAM UPAYA MENDUKUNG PELAKSANAAN OTONOMI DAERAH DI PROPINSI LAMPUNG - Syamsurijal AK; Suhel Suhel; Nuke Dina Apriyanti (Department of Development Economics, Universitas Sriwijaya, 2005)
The aims of this research are to know and to analyze of result from Sectors economy Strategic in effor to support implementing of local autonomy on Lampung Province. Theoretical framework based on Lincoln arsyad (1998); HF. Wiliamson (2000);Handoyo Pamudji (1988); Kenneth Davey (2000). The unit of analyzes method is quantitative approaches with uses location Quotients Analyzes (LQ), Contribution of best sectors and Effort tax for seeing of taken government prospect as ono as component who part in implementing of local autonomy. Result of the test indicates that from potent who lampung potent to have with use LQ analyzes with nine sectors economy can conclude that basis economy and have potent who can be value for economy of Lampung for 1993 – 2002 are agriculture sector, cattle raising sector, and forestry sector (2.158), construction sector (1.225), Transportation sector (1.108)and service sector (1.024). So from all basis sectors with PDRB, LQ value bigger than one (LQ>1). Contribution of basis sector with average 61.44 is bigger than non basis sectors with average 38.5878. So that include that for all from tax effort can to know that element of income region who given big contribution is from tax region so that PDRB one region to increase so ability region to pay tax from indirect can support implementing of local autonomy Lampung province. Keywords: Sector Economy Strategic, Basis Economy ,Tax Effort, and Local Autonomy